Agriscience fundamentals & applications - Cooper, Elmer L. (Albany Delmar Publishers, 1997)
An agriscience textbook exploring such topics as environmental technology, plant sciences, integrated pest management, interior and exterior plantscape, animal sciences, food science, and agribusiness.
Includes index.
Keywords: Agriculture -- Juvenile literature; Agriculture